2009
DOI: 10.1007/s11431-009-0039-y
|View full text |Cite
|
Sign up to set email alerts
|

Bifurcation and chaos of the bladed overhang rotor system with squeeze film dampers

Abstract: To study the nonlinear dynamic behavior of the bladed overhang rotor system with squeeze film damper (SFD), a blade-overhang rotor-SFD model is formulated using the lumped mass method and the Lagrange approach. The cavitated short bearing model is employed to describe the nonlinear oil force of the SFD. To reduce the scale of the nonlinear coupling system, a set of orthogonal transformations is employed to decouple the one nodal diameter equations of blades, which are coupled with the dynamical equations of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The ellipticity ratiod is a key parameter in an elliptical bearing. In general, the dynamic responses at each bearing centre and disc have very similar behaviour as indicated in reference [19]. Therefore, in the following discussion, the dynamic behaviours of the left bearing centre are taken as a typical example.…”
Section: Case Study Ii: the Rotor-bearing System For A 200 Mw Turbine Setmentioning
confidence: 90%
“…The ellipticity ratiod is a key parameter in an elliptical bearing. In general, the dynamic responses at each bearing centre and disc have very similar behaviour as indicated in reference [19]. Therefore, in the following discussion, the dynamic behaviours of the left bearing centre are taken as a typical example.…”
Section: Case Study Ii: the Rotor-bearing System For A 200 Mw Turbine Setmentioning
confidence: 90%
“…During the operation of the steam turbine, the turbine blades are affected by the harsh environment such as high pressure, high temperature, high speed and working in wet condition. 5,6 Also, combined with the effect of centrifugal force, airflow excitation force and high-speed erosion of water droplets, turbine blades are prone to vibrate during operation, resulting in steam turbine accidents. 7,8 In these accidents, accidents caused by damage of turbine blades due to vibration account for the major of the total accidents.…”
Section: Introductionmentioning
confidence: 99%
“…Chun and Lee [20] studied the effects of blade parameters on the coupled vibration of the blade-rotor system. Cao et al [21] simplified the blade into a cantilever beam structure and deeply studied the dynamic model of the blade-rotor system with the consideration of the factors such as sliding bearing, squeeze film damper, and gyro effect, respectively. e influence of blade parameters on the dynamic characteristics of the system showed that the blade parameters have a significant influence on the bifurcation characteristics of the coupled system, and the blade would change the instability speed of the system.…”
Section: Introductionmentioning
confidence: 99%